Short-term treatment with tolfenamic acid improves cognitive functions in AD mice - Subaiea, Gehad M. (2013)
Tolfenamic acid lowers the levels of the amyloid precursor protein (APP) and amyloid beta (Aβ) when administered to C57BL/6 mice by lowering their transcriptional regulator specificity protein 1 (SP1). To determine whether changes upstream in the amyloidogenic pathway that forms Aβ plaques would improve cognitive outcomes, we administered tolfenamic acid for 34 days to hemizygous R1.40 transgenic mice. Following the characterization of cognitive deficits in these mice, assessment of spatial learning and memory functions revealed that treatment with tolfenamic acid attenuated long-term memory and working memory deficits, determined using Morris water maze (MWM) and the Y-maze. These improvements occurred within a shorter period of exposure than that seen with clinically approved drugs. Cognitive enhancement was accompanied by reduction in the levels of the SP1 protein (but not mRNA), followed by lowering both the mRNA and protein levels of APP, and subsequent Aβ levels. These findings provide evidence that tolfenamic acid can disrupt the pathological processes associated with AD and are relevant to its scheduled biomarker study in AD patients.